2000
DOI: 10.1021/jp002145y
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and Mechanisms of Ultrafast Fluorescence Quenching Reactions of Flavin Chromophores in Protein Nanospace

Abstract: We have studied excited-state dynamics of “nonfluorescent” flavoproteins including riboflavin binding protein (RBP), d-amino acid oxidase benzoate complex (DAOB), and others by means of femtosecond fluorescence up-conversion method and have observed ultrafast fluorescence quenching dynamics for the first time. We have interpreted the fluorescence quenching mechanisms of these flavoproteins as due to the ultrafast electron transfer (ET) to flavin chromophore (F) in the excited electronic state from nearby trypt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
157
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(170 citation statements)
references
References 35 publications
13
157
0
Order By: Relevance
“…Through its influence on the electronic coupling, the ET rate k critically depends on the edge-to-edge distance r between the flavin cofactor and the quenching residue as k = k 0 e −βr (3,27). Assuming ET between Tyr and excited FAD is near barrierless (3,11), and β = 1.36 Å −1 (28), we can convert the lifetime distribution (Fig. 3C) to a distribution of distances from which ET takes place (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Through its influence on the electronic coupling, the ET rate k critically depends on the edge-to-edge distance r between the flavin cofactor and the quenching residue as k = k 0 e −βr (3,27). Assuming ET between Tyr and excited FAD is near barrierless (3,11), and β = 1.36 Å −1 (28), we can convert the lifetime distribution (Fig. 3C) to a distribution of distances from which ET takes place (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Experimentally, we exploited the fact that photoexcited FAD (FAD*) can accept an electron from the aromatic residues Tyr and Trp on the femtosecond-to-nanosecond timescale, and showed that in the case of TmThyX from, Tyr-91 is the principal electron donor. It has been argued that the FAD*Tyr→FAD − Tyr°+ reaction occurs with a driving force in the range of 0.7-1 eV and in a near-activationless regime (3,11). Indeed, the rates of this electron transfer reaction were found to be temperature independent in flavoproteins with a much less heterogeneous fluorescence decay distribution than TmThyX (11, 13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the pattern of positive and negative absorbance changes shows distinctive differences: the intensive negative signal of the stimulated emission at 520 -600 nm observed for free riboflavin in aqueous solution is missing for HsDod A -bound riboflavin (2), and the positive signal does not reach that far into the long wavelength region above 700 nm. A discussed mechanism for the fast quenching of the excited state, on the basis of previous investigations on flavoproteins (9,18,19), is an ultrafast electron transfer from a tryptophan residue to the excited flavin. If such an electron transfer occurs, the spectrum should show the absorption characteristics of a cationic tryptophan radical, expected around 560 nm (38,39) and of an anionic flavosemiquinone around 510 nm (40 -42).…”
Section: Resultsmentioning
confidence: 99%
“…Time-resolved fluorescence spectroscopy of flavins and flavoproteins has been reviewed by Berg and Visser (2001). However, a number of flavoproteins are practically non-fluorescent, but rather they emit fluorescence with very short lifetimes (sub-picoseconds) upon excitation with an ultra-short laser pulse (Mataga et al, 1998(Mataga et al, , 2000(Mataga et al, , 2002Tanaka et al 2007;Chosrowjan et al, 2007Chosrowjan et al, , 2008Chosrowjan et al, , 2010. In these flavoproteins tryptophan (Trp) and/or tyrosine (Tyr) residues always exist near the isoalloxazine ring (Iso).…”
Section: Introductionmentioning
confidence: 99%